(3GdJLGQI GdNGQLjI , GdUGOQGJ h GdhGQOGJ , GdJYQjaI GdLeQcjI , GdShb GdYQHjI GdeTJQcI h XGgQI GdYhdeIs - (3CTQa CMeO(B, (3GdYOdjs ((3GdGScfOQjI(B:s (3eDSSI QFjI(B,s, 2006)
(3eaghe h fXQjGJ GdJLGQI GdOhdjI , GdejRGf GdJLGQj GdOhdj h XGgQI GdYhdeI , MQjI h MeGjI GdJLGQI GdOGNdjI h GdNGQLjI , GdJYQjaI GdLeQcjI h GdgOa efgG h bhGYO JWHjb gPg GdJYQjaI , GdGShGb GdYQHjI h GdGJMGOGJ GdGbJUGOjI , CTcGd GdJYGhf GdGbJUGOj GdOhdj h GdGJLGg fMh Shb YQHjI eTJQcI HOhf MhGLR LeQcjI(B.s
Keywords: (3GdGbJUGO GdOhdjs; (3GdJLGQIs; (3GdJLGQI GdNGQLjIs; (3GdJUOjQs